Foot strike patterns in runners wearing floating heel, minimilist and conventional footwear - Barnes, A.; Paya, J. G.; Castelli, A.; Heller, B. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was investigate the vertical loading rate and footstrike angles when running in floating heel shoes (a new concept called FBR (Faster and Better Runners) compared to conventional and minimalist shoes. Footstrike angle and force data were collected from 15 male recreational runners as they ran in three different footwear conditions, floating heel, conventional and minimalist shoes. Results revealed that running in floating heel shoes promotes a non-rearfoot strike and results in reduced vertical loafing rates compared to both conventional and minimalist footwear. These findings suggest that floating heel shoes may offer a new way of running with a nonrearfoot strike without the risk of impact related injuries.